Determinants of energy security for rural households: The case of Melani and Hamburg communities, Eastern Cape, South Africa. Issue 4 (1st October 2020) - Ningi, Thulani; Taruvinga, Amon; Zhou, Leocadia
ABSTRACT: Energy plays critical direct and indirect roles in the livelihoods of human beings. Despite its relevance, the literature highlights that a majority of rural households are energy insecure and very much rely on unclean energy sources that compromise their health. Against this background, this paper estimates the determinants of energy security at the household level based on evidence from Melani-inland and Hamburg-coastal communities in the rural Eastern Cape Province of South Africa. The study used the multidimensional energy poverty index (MEPI) to calculate the energy security status of households in the two communities while the Tobit regression model was used to investigate the main factors affecting household energy security. The results indicated that in both communities, households were energy secure. However, access to additional energy measures was low, which could affect their energy security if the primary source (ESKOM electricity) is interrupted. Tobit regression results revealed that factors like marital status, household size, electricity affordability and source of income are the most critical factors influencing the energy security status of households in the study areas. Therefore, the paper recommends policy options that improve access of rural households to additional measures on energy and affordability of electricity.